Tzvetan Stoyanov and the Utopia of World Literature - Spassova, Kamelia (Acta Nova Humanistica: A Journal of Humanities Published by New Bulgarian University, 2025)
This article explores Tzvetan Stoyanov’s intellectual utopia of world literature as a counterpoint to the vale literature (kotlovinna literatura) debate of the 1960s. While contemporaries such as Toncho Zhechev and Krastyo Kuyumdzhiev defended the rootedness of national identity, Stoyanov envisioned Bulgarian literature as a participant in a “concert of nations”. Drawing on Goethe’s Weltliteratur ideal, he criticized three threats ‒ global homogenization, cultural isolationism and market-driven exoticization ‒ while practicing resistance through translations, critical and philosophical essays to bridge Bulgarian literature with the world literature canons. By reading the novel The Extraordinary Biography of Budi Budev (1969) as a parodic Bildungsroman, the paper reveals how Stoyanov transforms the Enlightenment ideal of education into a self-ironic allegory of intellectual resistance.